2015
DOI: 10.14245/kjs.2015.12.4.261
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Outcome in Patients with Cervical Spondylotic Myelopathy Undergoing Unilateral Open-Door Laminoplasty

Abstract: ObjectiveThis study aimed to analyze prognostic factors affecting surgical outcomes of expansive laminoplasty for cervical spondylotic myelopathy (CSM).MethodsUsing the Frankel scale and Japanese Orthopaedic Association (JOA) scale, we retrospectively reviewed the outcomes of 45 consecutive patients who underwent modified unilateral open-door laminoplasty using hydroxyapatite spacers and malleable titanium miniplates between June 2008 and May 2014. The patients were assigned to the good and poor clinical outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Several studies showed that laminoplasty reduced cervical ROM in various degrees [34,35,[37][38][39][40]. As shown in Table 2, it seems that the preservation of C2 and C7 muscle attachments have an important role in the preservation of cervical ROM postoperatively.…”
Section: Radiological Outcomementioning
confidence: 97%
See 4 more Smart Citations
“…Several studies showed that laminoplasty reduced cervical ROM in various degrees [34,35,[37][38][39][40]. As shown in Table 2, it seems that the preservation of C2 and C7 muscle attachments have an important role in the preservation of cervical ROM postoperatively.…”
Section: Radiological Outcomementioning
confidence: 97%
“…Most of these studies used the JOA score as a parameter of clinical outcome. They reported that laminoplasty provided significant enhancement of the JOA score in the short-term, mid-term, and long-term follow-up [34][35][36][37][38][39]. However, Sakaura et al [40] reported that the average JOA score was at its highest point in 12 months of follow-up and decreased slightly to 14.9 in the final follow-up.…”
Section: Clinical Outcomementioning
confidence: 98%
See 3 more Smart Citations